Endoscopic Hemostatic Treatment for Acute Gastrointestinal Bleeding by Combined Modality Therapy with PuraStat and Endoscopic Hemoclips - Kimitoshi Kubo; Shuhei Hayasaka; Ikko Tanaka (Case Reports in Gastroenterology, 2023)
Acute gastrointestinal bleeding (AGIB) is a common condition leading to hospitalization and is associated with significant morbidity and mortality. Various endoscopic treatments have been reported for AGIB, while its endoscopic hemostasis treatment by combined modality with PuraStat and endoscopic hemoclips remains less well documented. We report 6 cases of AGIB, i.e., 5 cases of ulcer bleeding and 1 case of ruptured gastric varices in 3 males and 3 females aged 49–97 years (mean age, 77 years), 2 and 1 of whom had been on antithrombotic drugs and nonsteroidal anti-inflammatory drugs, respectively, with 2 of these found to be in critical condition with hemorrhagic shock. Types of bleeding treated included oozing bleeding from visible vessels (n = 3), spurting bleeding from visible vessels (n = 2) and from gastric varices (n = 1). In all cases, complete hemostasis was achieved with no rebleeding. To our knowledge, this report represents a valuable addition to the AGIB literature describing endoscopic hemostasis by combined modality therapy with PuraStat and endoscopic hemoclips.